2022
DOI: 10.1108/bfj-12-2021-1337
|View full text |Cite
|
Sign up to set email alerts
|

Cultural food distancing: a conceptual discourse on the evolution of seminal to present and future models of traditional food practices

Abstract: PurposeThis manuscript focuses on theoretical past, present and future models for defining food culture and cuisine, comparing these principles with contemporary literature evidence of transformative global food practices during public health and environmental crisis. The purpose of this study, therefore, is to explain the point at which traditional practices are discernible from the effects of modern technology, globalization, marketing and the virtualization of consumption. The paper explains how current loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 92 publications
(205 reference statements)
0
2
0
Order By: Relevance
“…When studies on food preference are examined, local food (Viciunaite, 2023;Aprile and Fiorillo, 2023;Meyerding et al, 2019), organic food ( Colovi c and Miti c, 2023), consumer behavior (Reshi et al, 2023), sustainability (Gracia and Gomez, 2020;Isaak andLentz, 2020, andculture (Feldman andWunderlich, 2023) are discussed. This typology indicates that digital nomads' food preferences are not solely based on the pursuit of taste; they are also closely related to cultural exploration, health consciousness, and sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…When studies on food preference are examined, local food (Viciunaite, 2023;Aprile and Fiorillo, 2023;Meyerding et al, 2019), organic food ( Colovi c and Miti c, 2023), consumer behavior (Reshi et al, 2023), sustainability (Gracia and Gomez, 2020;Isaak andLentz, 2020, andculture (Feldman andWunderlich, 2023) are discussed. This typology indicates that digital nomads' food preferences are not solely based on the pursuit of taste; they are also closely related to cultural exploration, health consciousness, and sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…Stalmirska (2023) argues that for local populations to improve the variety of cuisines available in their regions, they need to change their attitudes toward foods from other cultures. Despite this, recent research has shown that many people still value the authenticity and traditional components of their local cuisine (Feldman & Wunderlich, 2023).…”
Section: B Globalization Has Led To An Increase In Cultural Diversitymentioning
confidence: 99%